A flexible alloy siloxane composite weather-resistant anticorrosion coating for steel structure and preparation method thereof
Through the flexible alloy silicone composite weather-resistant and anti-corrosion coating system, the existing coatings have been solved, and the existing coatings have insufficient self-repair capabilities and poor shielding performance have been achieved, which has achieved higher anti-corrosion performance and service life, and is suitable for steel structure protection in complex environments.
Patent Information
- Application Number
- CN202411930162.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing steel structure anticorrosion coating system has problems such as insufficient self-repair capability, weak shielding performance and prone to lateral copolymerization damage during long-term use, resulting in weakening of the electrochemical protection effect and short service life.
The flexible alloy siloxane composite weather-resistant and anti-corrosion coating system is adopted, including flexible alloy coating, alloy enclosed coating and amino-modified silane topcoat coating. It uses high-density tough resin, composite alloy powder and rare earth materials to form a dual protection mechanism, and enhances the weather resistance and corrosion resistance of the coating through hydrophobic modification and anti-ultraviolet coating.
It significantly improves the shielding and weathering properties of the coating, extends the service life of the steel structure, enhances its protection ability in complex environments, and reduces the risks of corrosion and mechanical damage.
Smart Images

Figure CN119350904B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion coatings, in particular to a flexible alloy-siloxane composite weather-resistant anti-corrosion coating for a steel structure and a preparation method thereof. Background Art
[0002] Long-term anti-corrosion protection for steel structures usually adopts a coating system design of "primer + intermediate paint + topcoat", such as "epoxy zinc-rich primer + epoxy intermediate paint + acrylic topcoat", "inorganic zinc-rich primer + epoxy intermediate paint + acrylic polyurethane topcoat", etc. However, although these coating systems have been widely recognized in design and application, their design life is not long.
[0003] Although these coating systems use zinc-rich primers with excellent electrochemical protection performance, their main component, zinc powder, is used as an anti-rust pigment, which makes the anti-corrosion mechanism relatively simple. This single anti-corrosion mechanism makes the coating lack self-repairing ability when dealing with corrosive environments, and the shielding performance is insufficient, which easily leads to the occurrence of lateral copolymerization damage. This phenomenon will further weaken the electrochemical protection effect of the coating, making it face the risk of failure in long-term use.
[0004] Secondly, in terms of the choice of topcoat for these coatings, the commonly used room temperature curing polyurethane topcoat is mainly composed of hydroxyl acrylic resin and isocyanate curing agent. Although it has a certain wide range of applications, its defects such as low molecular bond energy and easy degradation limit its long-term performance. Therefore, in order to improve the anti-corrosion protection effect of steel structures and extend their service life, it is necessary to conduct in-depth research and improve the existing coating system design. This includes optimizing the selection of primers and topcoats to improve the shielding performance and weather resistance of the coating to ensure that it can still effectively protect the steel structure in complex environments. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure and its preparation method. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure includes a flexible alloy coating, an alloy sealing coating and an amino-modified silane topcoat coating arranged in sequence on the surface of the steel structure: the flexible alloy coating utilizes the physical shielding properties of high-density tough resin to effectively prevent the penetration of corrosive media, and at the same time, composite alloy powder is used in the flexible alloy coating to replace zinc powder, enriching the anti-corrosion mechanism and enhancing its anti-corrosion performance. The salt inorganic matter in the alloy inhibits the ionization corrosion behavior of the metal when the corrosive medium contacts the alloy, forming a double protection mechanism; the alloy sealing coating uses flaky materials to form a unique shielding layer to limit the diffusion of corrosive media in the coating, and at the same time, it also improves the toughness of the coating, making the coating more durable and able to maintain a long-term and stable protective effect in various harsh environments; through fluorination modification, a hydrophobic protective layer can be formed on the surface of the weather-resistant filler to enhance its anti-corrosion performance, and the use of anti-ultraviolet resin coating can effectively prevent ultraviolet damage to the filler and substrate, and extend the service life of the filler and coating.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a flexible alloy-siloxane composite weather-resistant anti-corrosion coating for a steel structure, wherein the flexible alloy-siloxane composite weather-resistant anti-corrosion coating for a steel structure comprises a flexible alloy coating, an alloy sealing coating and an amino-modified silane topcoat coating sequentially arranged on the surface of the steel structure, wherein the sum of the dry film thicknesses of the flexible alloy coating, the alloy sealing coating and the amino-modified silane topcoat coating is 200-300 μm;
[0008] Preferably, the dry film thickness of the flexible alloy coating is 60-100 μm;
[0009] Preferably, the dry film thickness of the alloy sealing coating is 80-120 μm;
[0010] Preferably, the dry film thickness of the amino-modified silane topcoat coating is 60-80 μm.
[0011] The flexible alloy coating comprises ultra-high molecular weight conductive epoxy modified resin, composite alloy powder and rare earth material;
[0012] The alloy sealing coating comprises epoxy resin, glass flakes, modified flaky mica and amine curing agent;
[0013] The amino-modified silane topcoat coating comprises a modified silane resin, a fluorinated weather-resistant filler coated with an anti-ultraviolet coating, a diluent and an aminosilane curing agent.
[0014] As a preferred technical solution of the present invention, the sum of the dry film thicknesses of the flexible alloy coating, the alloy sealing coating and the amino-modified silane topcoat coating is 200-300 μm, for example, it can be 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm or 300 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In some optional examples, the dry film thickness of the flexible alloy coating is 60-100 μm, for example, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In some optional examples, the dry film thickness of the alloy sealing coating is 80-120 μm, for example, it can be 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm or 120 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional examples, the dry film thickness of the amino-modified silane topcoat coating is 60-80 μm, for example, it can be 60 μm, 62 μm, 64 μm, 66 μm, 68 μm, 70 μm, 72 μm, 74 μm, 76 μm, 78 μm or 80 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] As a preferred technical solution of the present invention, in a flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure, the flexible alloy coating comprises the following components in parts by weight:
[0019] 3-10 parts of ultra-high molecular weight conductive epoxy modified resin;
[0020] Composite alloy powder 70-95 parts;
[0021] 1-10 parts of rare earth materials.
[0022] In some optional examples, the mass proportion of the ultra-high molecular weight conductive epoxy modified resin is 3-10 parts, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional instances, the mass proportion of the composite alloy powder is 70-95 parts, for example, it can be 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts or 95 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional examples, the mass proportion of the rare earth material is 1-10 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In flexible alloy coatings, ultra-high molecular weight conductive epoxy modified resin plays a key role. This resin not only has a high cross-linking density, which makes the network structure formed after curing relatively dense, but also has a certain toughness. This high cross-linking density feature enables the coating to effectively form an electrochemical protection barrier to block the invasion of corrosive media, thereby providing excellent shielding effect and improving the corrosion resistance of the coating. In addition, the toughness of this resin ensures that after mixing with composite alloy powder and rare earth materials, the coating is not easy to crack in actual use, and can withstand the challenges brought by temperature changes and mechanical stress, thereby reducing the occurrence of cracking or peeling, and ensuring the overall integrity and service life of the coating.
[0026] In the selection of anti-rust pigments, the application of composite alloy powders enhances the anti-corrosion ability of the coating. These alloy powders can not only effectively provide cathodic protection, but also activate the inorganic salts in the alloy when the corrosive medium contacts the alloy through the physical barrier. These salts inhibit the ionization corrosion behavior of the metal through chemical reactions, thereby slowing down or preventing the further development of the corrosion process, forming a multiple protection mechanism. This multiple protection can effectively improve the durability of the coating in harsh environments and ensure that the metal structure is fully protected.
[0027] The introduction of rare earth materials provides a guarantee for the improvement of coating performance. Rare earth materials such as lanthanum oxide and cerium trichloride have excellent heat resistance and weather resistance, which can improve the coating's oxidation resistance and ability to resist ultraviolet rays, thereby further extending the service life of the coating. The stability and efficiency of these materials enable the coating to maintain good performance even after long-term exposure to various climatic conditions.
[0028] By combining the advantages of ultra-high molecular weight conductive epoxy modified resin, composite alloy powder and rare earth materials, this composite material not only fully utilizes the physical shielding properties of high-density tough resin to effectively block the penetration of corrosive media into the metal surface, but also enhances the durability and stability of the coating. This scientific and reasonable combination provides long-lasting and effective protection for various metal structures, ensuring that they can still maintain good performance in changing and harsh environments and extend their service life.
[0029] As a preferred technical solution of the present invention, in a flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure, the alloy sealing coating comprises the following components in parts by weight:
[0030] Epoxy resin 10-30 parts;
[0031] Glass flakes 20-35 parts;
[0032] 10-30 parts of modified flaky mica;
[0033] 20-50 parts of amine curing agent.
[0034] In some optional examples, the mass parts of epoxy resin are 10-30 parts, for example, it can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional instances, the mass proportion of glass flakes is 20-35 parts, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the mass proportion of the modified flaky mica is 10-30 parts, for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, the mass parts of the amine curing agent are 20-50 parts, for example, it can be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts or 50 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Epoxy resins, due to their excellent adhesion, can form strong adhesion with a variety of substrates, effectively prevent the penetration of moisture and corrosive media, and provide long-lasting protection. Epoxy resins (such as E51 epoxy resin, E20 epoxy resin, and E44 epoxy resin) have high mechanical strength and toughness and can resist external impact and stress. This property enables the coating to maintain stability in the face of environmental factors such as temperature changes and mechanical vibrations, reducing the risk of cracks and peeling.
[0039] The fillers are made of flaky materials such as glass flakes and flaky mica. These flaky structures form a unique shielding layer in the coating. The parallel overlapping and interlaced characteristics greatly restrict the diffusion of corrosive media such as water and ions in the coating, thereby enhancing the protective performance of the coating. In addition, this flaky coating structure also improves the toughness of the coating. When the coating is subjected to external forces, these flaky materials can effectively disperse and transfer stress, reducing the risk of cracking and damage to the coating. This improves the durability and long-term stability of the coating in harsh environments.
[0040] The flaky mica is modified by introducing hydrophobic groups. The introduction of hydrophobic groups effectively reduces the penetration of water in the coating. It is difficult for water molecules to penetrate the hydrophobic layer, thereby reducing the possibility of water entering the deep layer of the coating and the surface of the substrate, and reducing the risk of corrosion reactions. During the electrochemical corrosion process, the migration of water and electrolytes will cause corrosion of the metal substrate, and the hydrophobically modified mica can effectively reduce the penetration of water and salt spray, block the corrosion factors from contacting the substrate surface, and enhance the anti-corrosion performance.
[0041] After the hydrophobic groups are introduced, a polydimethylsiloxane coating is further introduced on the surface of the hydrophobic flaky mica. The polydimethylsiloxane coating has low surface energy and high chemical stability, and can form a uniform hydrophobic protective layer on the mica sheet, further improving the shielding performance of the coating. At the same time, the polydimethylsiloxane coating can fill the micropores and surface irregularities of the mica sheet, provide a smooth and uniform interface, and help reduce micro defects in the coating that may cause cracks and peeling. In addition, polydimethylsiloxane also has the characteristics of high temperature resistance and UV resistance, which can effectively resist the degradation caused by ultraviolet radiation, reduce the aging and powdering problems of the coating under long-term sunlight exposure, thereby improving the long-term weather resistance of the coating. At the same time, the polydimethylsiloxane coating has good compatibility in the organic resin system, which makes the modified flaky mica more closely combined with components such as epoxy resin and curing agent, thereby improving the weather resistance and anti-corrosion performance of the overall coating.
[0042] Amine curing agents can chemically react with epoxy resins to form a cross-linked structure, thereby enhancing the durability and thermal stability of the coating. This curing mechanism enables the coating to perform well in a variety of application environments, ensuring its long-term effectiveness.
[0043] As a preferred technical solution of the present invention, in a flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure, the amino-modified silane topcoat coating comprises the following components in parts by weight:
[0044] 40-60 parts of modified silane resin;
[0045] 30-50 parts of fluorinated weather-resistant filler coated with UV-resistant coating;
[0046] 10-30 parts of diluent;
[0047] 20-30 parts of aminosilane curing agent.
[0048] In some optional examples, the mass parts of the modified silane resin are 40-60 parts, for example, it can be 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts or 60 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional examples, the mass proportion of the fluorinated weather-resistant filler coated with the anti-ultraviolet coating is 30-50 parts, for example, it can be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts or 50 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional examples, the mass proportion of the diluent is 10-30 parts, for example, it can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the mass parts of aminosilane curing agent are 20-30 parts, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Modified silane resins, such as silicone epoxy modified resin SJ-804, acrylic polysiloxane resin B6425, and polyether modified silane resin XT-50, have excellent resistance to UV rays, high temperatures, and chemical corrosion. This allows the coating to maintain stable performance and appearance in harsh environments exposed to sunlight, humidity, and temperature changes, extending the service life of the coating; at the same time, modified silane resins perform well in bonding with the surface of the substrate, and their chemical properties enable them to form strong adhesion with a variety of materials, thereby effectively reducing peeling and shedding.
[0053] Weathering fillers such as barium sulfate, silicon carbide, feldspar powder and glass powder can provide a physical barrier to limit the penetration of moisture, ions and other corrosive media. The selection of these fillers enhances the anti-corrosion effect of the coating and enables it to resist chemical attack in the environment.
[0054] The weather-resistant filler is modified by using a fluorinating agent. The fluorinating agent usually has strong hydrophobicity and can form a hydrophobic protective layer on the surface of the filler. This hydrophobic layer can reduce the penetration of water and other liquids, thereby reducing the possibility of corrosive media contacting the substrate and enhancing the anti-corrosion performance. At the same time, the surface of the weather-resistant filler after fluorination modification can reduce the adhesion of water, and the migration and accumulation of water in the coating are effectively inhibited, reducing the electrochemical corrosion caused by water.
[0055] Anti-UV resin is coated on the surface of weather-resistant filler, providing it with an effective protective barrier that can absorb and scatter UV radiation, preventing UV damage to filler and substrate. This protection mechanism not only extends the service life of the filler, but also ensures the stability of the coating under sunlight; and the coating of anti-UV resin can reduce the photodegradation reaction caused by UV rays, thereby improving the weather resistance of the coating, allowing it to maintain good physical and chemical properties under long-term sunlight exposure.
[0056] There is also a synergistic effect between fluorination modification and coating with UV-resistant resin: the hydrophobicity of the fluorination agent combined with the protective effect of the UV-resistant resin forms a multiple protection mechanism. Fluorination modification provides a physical barrier to prevent the penetration of moisture and corrosive media, while the UV-resistant resin provides chemical protection to prevent UV damage to the filler. This synergistic effect enhances the overall performance of the coating; the joint modification of the fluorination agent and the UV-resistant resin helps to improve the compatibility of the modified filler with substrates such as epoxy resins, thereby improving its adhesion. Good adhesion can reduce coating peeling and blistering, ensuring the integrity and long-term effect of the coating.
[0057] Diluents such as toluene, xylene, butyl acetate, and propylene glycol methyl ether acetate can adjust the viscosity and leveling properties of the coating to adapt it to different coating processes and application requirements while ensuring the uniformity and smoothness of the coating.
[0058] Aminosilane curing agents can react with modified silane resins to form a cross-linked network, thereby improving the hardness, durability and impact resistance of the coating. This cross-linked structure enables the coating to maintain good integrity when facing mechanical stress and environmental changes. In addition, modified silane resins and aminosilane curing agents generally have lower volatile organic compound emissions, which helps reduce environmental pollution and potential health hazards, and is in line with the trend of green coatings.
[0059] In a second aspect, the present invention provides a method for preparing a flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for a steel structure, the preparation method comprising:
[0060] S1: Mix and stir the ultra-high molecular weight conductive epoxy modified resin, composite alloy powder, rare earth material and xylene to form an anti-corrosion primer, and continuously spray the anti-corrosion primer on the surface of the steel structure substrate to form a flexible alloy coating;
[0061] S2: preparing a chlorohexadecane ethanol solution, soaking the flaky mica in the chlorohexadecane ethanol solution, filtering, washing, and drying to obtain hydrophobic flaky mica; dissolving polydimethylsiloxane in toluene to obtain a coating solution, soaking the hydrophobic flaky mica in the coating solution, taking it out and curing it to obtain modified flaky mica;
[0062] S3: mixing epoxy resin, glass flakes, modified flaky mica and xylene, stirring evenly to obtain alloy sealing coating material A, mixing alloy sealing coating material A with an amine curing agent evenly to obtain an anti-corrosion intermediate paint, and continuously spraying the anti-corrosion intermediate paint on the surface of the steel structure substrate coated with the flexible alloy coating to form an alloy sealing coating;
[0063] S4: preparing a fluorinating agent solution, adding a weather-resistant filler to the fluorinating agent solution, stirring and mixing, filtering, washing, and drying to obtain a fluorinated weather-resistant filler; mixing an anti-ultraviolet resin with anhydrous ethanol to obtain an anti-ultraviolet resin solution, adding the fluorinated weather-resistant filler to the anti-ultraviolet resin solution, stirring, filtering, and curing to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating;
[0064] S5: After the modified silane resin, the fluorinated weather-resistant filler coated with the anti-ultraviolet coating and the diluent are stirred and mixed evenly, the mixture is ground by a ball mill to obtain an anti-corrosion topcoat C material, the anti-corrosion topcoat C material is mixed evenly with the aminosilane curing agent to obtain an anti-corrosion topcoat, and the anti-corrosion topcoat is continuously sprayed on the surface of the steel structure substrate coated with the alloy sealing coating to form an amino-modified silane topcoat coating.
[0065] As a preferred technical solution of the present invention, in S1, the solid content of the anti-corrosion primer is 15-30%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] As a preferred technical solution of the present invention, in S2, the mass fraction of the hexadecyl chloride ethanol solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] In some optional examples, the mass ratio of hexachlorodecane to flaky mica is 1:(10-15), for example, it can be 1:10.0, 1:10.5, 1:11.0, 1:11.5, 1:12.0, 1:12.5, 1:13.0, 1:13.5, 1:14.0, 1:14.5 or 1:15.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] In some optional examples, the mass fraction of the coating solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the mass ratio of the polydimethylsiloxane to the hydrophobic flaky mica is 1:(5-10), for example, it can be 1:5.0, 1:5.5, 1:6.0, 1:6.5, 1:7.0, 1:7.5, 1:8.0, 1:8.5, 1:9.0, 1:9.5 or 1:10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] As a preferred technical solution of the present invention, in S3, the solid content of the alloy sealing coating A material is 15-25%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] As a preferred technical solution of the present invention, in S4, the mass fraction of the fluorinating agent solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In some optional examples, the mass ratio of the fluorinating agent to the weather-resistant filler is (1-2):100, for example, it can be 1.0:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100 or 2.0:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In some optional examples, the mass fraction of the UV resistant resin solution is 10-20wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the mass ratio of the UV resistant resin to the fluorinated weather-resistant filler is (1-2):10, for example, it can be 1.0:10, 1.1:10, 1.2:10, 1.3:10, 1.4:10, 1.5:10, 1.6:10, 1.7:10, 1.8:10, 1.9:10 or 2.0:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] Compared with the prior art, the present invention has the following beneficial effects:
[0076] (1) Composite alloy powder is used instead of zinc powder in the flexible alloy coating. The composite alloy powder can effectively provide cathodic protection, and the salt inorganic substances in the composite alloy powder inhibit the ionization corrosion behavior of the metal when the corrosive medium contacts the alloy, forming a dual protection mechanism;
[0077] (2) The alloy sealing coating uses flaky materials to form a unique shielding layer, which limits the diffusion of corrosive media in the coating and improves the toughness of the coating. The introduction of hydrophobic groups and polydimethylsiloxane coatings can further enhance the weather resistance and corrosion resistance of the flaky mica, thereby improving the weather resistance and corrosion resistance of the overall coating.
[0078] (3) In the amino-modified silane topcoat coating, a hydrophobic protective layer can be formed on the surface of the weather-resistant filler through fluorination modification, thereby enhancing its anti-corrosion performance. The use of anti-ultraviolet resin coating can effectively prevent ultraviolet rays from damaging the filler and substrate, thereby extending the service life of the filler and coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 A schematic diagram of the structure of a flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for steel structures provided by the present invention;
[0080] Figure 2 A flow chart of a method for preparing a flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for a steel structure provided in Examples 1 to 4 of the present invention.
[0081] Figure numerals: 1. flexible alloy coating; 2. alloy sealing coating; 3. amino-modified silane topcoat coating; 4. steel structure substrate. DETAILED DESCRIPTION
[0082] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0083] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows:
[0084] Conductive polyaniline: purchased from Shanghai Gaoming Chemical Co., Ltd.
[0085] Acrylic acid modified epoxy conjugated resin: purchased from Guangdong Keding Functional Materials Co., Ltd.;
[0086] Zinc-aluminum alloy: purchased from Hunan Jinhao New Materials Technology Co., Ltd.;
[0087] Magnesium aluminum alloy: purchased from Tangshan Weihao Magnesium Powder Co., Ltd.;
[0088] Copper-zinc alloy: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0089] Magnesium-zinc alloy: purchased from Tangshan Weihao Magnesium Powder Co., Ltd.;
[0090] Magnesium-lithium alloy: purchased from Luoyang Jushen High Performance Alloy Materials Co., Ltd.;
[0091] Lanthanum oxide: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0092] Cerium trichloride: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0093] E51 epoxy resin: purchased from Jiangsu Sanmu Group Co., Ltd.;
[0094] E20 epoxy resin: purchased from Jiangsu Sanmu Group Co., Ltd.;
[0095] E44 epoxy resin: purchased from Jiangsu Sanmu Group Co., Ltd.;
[0096] Glass flakes: purchased from Nolson Chemical Company;
[0097] Chlorohexadecane: purchased from Shijiazhuang Kechen Chemical Co., Ltd.;
[0098] Flake mica: 5000 mesh, purchased from Chuzhou Ge Rui Mining Co., Ltd.;
[0099] Polydimethylsiloxane: purchased from Jinan Longcheng Silicone Co., Ltd.;
[0100] Polyamide curing agent 650: purchased from Guangzhou Yuanda New Materials Co., Ltd.;
[0101] Cardanol curing agent: purchased from Shanghai Zhengxi Material Technology Co., Ltd.;
[0102] Silicone epoxy modified resin SJ-804: purchased from Guangdong Shanjin New Materials Co., Ltd.;
[0103] Acrylic polysiloxane resin B6425: purchased from Dongguan Aibao Nano Technology Co., Ltd.;
[0104] Polyether modified silane resin XT-50: purchased from Wacker Chemie Co., Ltd.;
[0105] Ammonium fluoride: purchased from Yonghua Chemical Co., Ltd.
[0106] Calcium fluoride: purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0107] Barium sulfate: purchased from Shanghai Yien Chemical Technology Co., Ltd.;
[0108] Silicon carbide: purchased from Zhejiang Yamei Nano Technology Co., Ltd.;
[0109] Feldspar powder: purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0110] Glass powder: purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0111] Acrylic resin: purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0112] Polyurethane resin: purchased from Huachang Polymer Co., Ltd., East China University of Science and Technology;
[0113] Toluene: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0114] Xylene: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0115] Anhydrous ethyl ester: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0116] Butyl acetate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0117] Propylene glycol methyl ether acetate: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0118] 3-Acryloxypropyltrimethoxysilane: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0119] Bis-[3-(triethoxysilyl)propyl]amine: purchased from Nanjing Nengde New Materials Technology Co., Ltd.;
[0120] N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane: purchased from Nanjing Quanxi New Materials Co., Ltd.
[0121] Example 1
[0122] This embodiment provides a flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure. Figure 1 The flexible alloy-siloxane composite weather-resistant anticorrosion coating for steel structure comprises a flexible alloy coating 1 with a thickness of 60 μm, an alloy sealing coating 2 with a thickness of 100 μm and an amino-modified silane topcoat coating 3 with a thickness of 80 μm, which are sequentially arranged on the surface of a steel structure substrate 4. The sum of the dry film thicknesses of the flexible alloy coating 1, the alloy sealing coating 2 and the amino-modified silane topcoat coating 3 is 240 μm.
[0123] This embodiment also provides a method for preparing a flexible alloy siloxane composite weather-resistant anti-corrosion coating for a steel structure, see Figure 2 , the preparation method specifically comprises the following steps:
[0124] S1: 3g of conductive polyaniline, 20g of zinc-aluminum alloy, 23g of magnesium-aluminum alloy, 27g of magnesium-zinc alloy, 1g of cerium trichloride, and 20g of xylene are mixed and stirred evenly to form an anti-corrosion primer, and the anti-corrosion primer is continuously sprayed on the surface of the steel structure substrate 4 to form a flexible alloy coating 1, wherein the thickness of the flexible alloy coating 1 is 60 μm;
[0125] S2: preparing a 5wt% ethanol solution of hexadecane chloride, soaking the flaky mica in the ethanol solution of hexadecane chloride, wherein the mass ratio of hexadecane chloride to the flaky mica is 1:10, filtering, washing, and drying to obtain hydrophobic flaky mica; dissolving polydimethylsiloxane in toluene to obtain a coating solution with a mass fraction of 10wt%, soaking the hydrophobic flaky mica in the coating solution, wherein the mass ratio of polydimethylsiloxane to the hydrophobic flaky mica is 1:10, taking out and curing to obtain modified flaky mica;
[0126] S3: 10g of E20 epoxy resin, 30g of glass flakes, 10g of modified flaky mica and 10g of xylene are mixed and stirred to obtain alloy closed coating material A, and the alloy closed coating material A is mixed with 20g of polyamide curing agent 650 to obtain an anti-corrosion intermediate paint, and the anti-corrosion intermediate paint is continuously sprayed on the surface of the steel structure substrate 4 coated with the flexible alloy coating 1 to form an alloy closed coating 2, wherein the thickness of the alloy closed coating 2 is 100μm;
[0127] S4: prepare a 7wt% ammonium fluoride solution, add a weather-resistant filler to the ammonium fluoride solution, wherein the mass ratio of ammonium fluoride to weather-resistant filler is 1:100, stir and mix, filter, wash, and dry to obtain a fluorinated weather-resistant filler; mix acrylic resin with anhydrous ethanol to obtain a 10wt% acrylic resin solution, add the fluorinated weather-resistant filler to the acrylic resin solution and stir, wherein the mass ratio of acrylic resin to fluorinated weather-resistant filler is 2:10, filter, and cure to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating;
[0128] S5: Stir and mix 40g of acrylic polysiloxane resin B6425, 30g of barium sulfate fluoride coated with an anti-ultraviolet coating and 10g of anhydrous ethyl ester, grind and mix by ball mill to obtain anti-corrosion topcoat C, mix the anti-corrosion topcoat C with 25g of 3-acryloxypropyltrimethoxysilane to obtain an anti-corrosion topcoat, and continuously spray the anti-corrosion topcoat on the surface of the steel structure substrate 4 coated with the alloy sealing coating 2 to form an amino-modified silane topcoat coating 3, wherein the thickness of the amino-modified silane topcoat coating 3 is 80μm.
[0129] Example 2
[0130] This embodiment provides a flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure. Figure 1 The flexible alloy-siloxane composite weather-resistant anticorrosion coating for steel structure comprises a flexible alloy coating 1 with a thickness of 80 μm, an alloy sealing coating 2 with a thickness of 120 μm and an amino-modified silane topcoat coating 3 with a thickness of 60 μm, which are sequentially arranged on the surface of a steel structure substrate 4. The sum of the dry film thicknesses of the flexible alloy coating 1, the alloy sealing coating 2 and the amino-modified silane topcoat coating 3 is 260 μm.
[0131] This embodiment also provides a method for preparing a flexible alloy siloxane composite weather-resistant anti-corrosion coating for a steel structure, see Figure 2 , the preparation method specifically comprises the following steps:
[0132] S1: 10g of acrylic modified epoxy conjugated resin, 40g of copper-zinc alloy, 10g of magnesium-zinc alloy, 30g of zinc-aluminum alloy, 5g of magnesium-aluminum alloy, 10g of magnesium-lithium alloy, 10g of cerium trichloride, and 20g of xylene are mixed and stirred evenly to form an anti-corrosion primer, and the anti-corrosion primer is continuously sprayed on the surface of the steel structure substrate 4 to form a flexible alloy coating 1, wherein the thickness of the flexible alloy coating 1 is 80μm;
[0133] S2: preparing a 7.5wt% ethanol solution of hexadecane chloride, soaking the flaky mica in the ethanol solution of hexadecane chloride, wherein the mass ratio of hexadecane chloride to the flaky mica is 1:13, filtering, washing, and drying to obtain hydrophobic flaky mica; dissolving polydimethylsiloxane in toluene to obtain a coating solution with a mass fraction of 8wt%, soaking the hydrophobic flaky mica in the coating solution, wherein the mass ratio of polydimethylsiloxane to the hydrophobic flaky mica is 1:7, taking out and curing to obtain modified flaky mica;
[0134] S3: 20g of E44 epoxy resin, 35g of glass flakes, 30g of modified flaky mica and 15g of xylene are mixed and stirred to obtain alloy sealing coating material A, and the alloy sealing coating material A is mixed with 50g of cardanol curing agent to obtain an anti-corrosion intermediate paint, and the anti-corrosion intermediate paint is continuously sprayed on the surface of the steel structure substrate 4 coated with the flexible alloy coating 1 to form an alloy sealing coating 2, wherein the thickness of the alloy sealing coating 2 is 120μm;
[0135] S4: preparing a calcium fluoride solution with a mass fraction of 5wt%, adding a weather-resistant filler to the calcium fluoride solution, wherein the mass ratio of calcium fluoride to the weather-resistant filler is 1.5:100, stirring and mixing, filtering, washing, and drying to obtain a fluorinated weather-resistant filler; mixing a polyurethane resin with anhydrous ethanol to obtain a polyurethane resin solution with a mass fraction of 15wt%, adding the fluorinated weather-resistant filler to the polyurethane resin solution and stirring, wherein the mass ratio of the polyurethane resin to the fluorinated weather-resistant filler is 1.6:10, filtering, and curing to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating;
[0136] S5: 60g of polyether modified silane resin XT-50, 20g of barium sulfate fluoride coated with an anti-ultraviolet coating, 30g of silicon carbide fluoride coated with an anti-ultraviolet coating and 30g of butyl acetate are stirred and mixed evenly, and then the mixture is ground by a ball mill to obtain an anti-corrosion topcoat C material. The anti-corrosion topcoat C material is mixed evenly with 30g of bis-[3-(triethoxysilyl)propyl]amine to obtain an anti-corrosion topcoat. The anti-corrosion topcoat is continuously sprayed on the surface of the steel structure substrate 4 coated with the alloy sealing coating 2 to form an amino-modified silane topcoat coating 3, and the thickness of the amino-modified silane topcoat coating 3 is 60μm.
[0137] Example 3
[0138] This embodiment provides a flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure. Figure 1 The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure comprises a flexible alloy coating 1 with a thickness of 100 μm, an alloy sealing coating 2 with a thickness of 80 μm and an amino-modified silane topcoat coating 3 with a thickness of 70 μm, which are sequentially arranged on the surface of a steel structure substrate 4. The sum of the dry film thicknesses of the flexible alloy coating 1, the alloy sealing coating 2 and the amino-modified silane topcoat coating 3 is 250 μm.
[0139] This embodiment also provides a method for preparing a flexible alloy siloxane composite weather-resistant anti-corrosion coating for a steel structure, see Figure 2 , the preparation method specifically comprises the following steps:
[0140] S1: 2g of acrylic acid-modified epoxy conjugated resin, 3g of conductive polyaniline, 80g of zinc-aluminum alloy, 13g of magnesium-aluminum alloy, 1g of lanthanum oxide, 2g of cerium trichloride, and 20g of xylene are mixed and stirred to form an anti-corrosion primer, and the anti-corrosion primer is continuously sprayed on the surface of the steel structure substrate 4 to form a flexible alloy coating 1, wherein the thickness of the flexible alloy coating 1 is 100 μm;
[0141] S2: preparing a 10wt% ethanol solution of hexadecane chloride, soaking the flaky mica in the ethanol solution of hexadecane chloride, wherein the mass ratio of hexadecane chloride to the flaky mica is 1:15, filtering, washing, and drying to obtain hydrophobic flaky mica; dissolving polydimethylsiloxane in toluene to obtain a coating solution of 5wt%, soaking the hydrophobic flaky mica in the coating solution, wherein the mass ratio of polydimethylsiloxane to the hydrophobic flaky mica is 1:5, taking out and curing to obtain modified flaky mica;
[0142] S3: 20g of E51 epoxy resin, 10g of E44 epoxy resin, 20g of glass flakes, 25g of modified flaky mica and 15g of xylene are mixed and stirred to obtain alloy sealing coating material A, and the alloy sealing coating material A is mixed with 35g of cardanol curing agent to obtain an anti-corrosion intermediate paint, and the anti-corrosion intermediate paint is continuously sprayed on the surface of the steel structure substrate 4 coated with the flexible alloy coating 1 to form an alloy sealing coating 2, wherein the thickness of the alloy sealing coating 2 is 80μm;
[0143] S4: prepare a 10wt% ammonium fluoride solution, add a weather-resistant filler to the ammonium fluoride solution, wherein the mass ratio of ammonium fluoride to weather-resistant filler is 2:100, stir and mix, filter, wash, and dry to obtain a fluorinated weather-resistant filler; mix a polyurethane resin with anhydrous ethanol to obtain a 20wt% polyurethane resin solution, add the fluorinated weather-resistant filler to the polyurethane resin solution and stir, wherein the mass ratio of the polyurethane resin to the fluorinated weather-resistant filler is 1:10, filter, and cure to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating;
[0144] S5: 25g of silicone epoxy modified resin SJ-804, 30g of polyether modified silane resin XT-50, 10g of fluorinated silicon carbide coated with an anti-UV coating, 20g of fluorinated feldspar powder coated with an anti-UV coating, 10g of fluorinated glass powder coated with an anti-UV coating and 15g of propylene glycol methyl ether acetate are stirred and mixed evenly, and then ground and mixed by ball milling to obtain an anti-corrosion topcoat C material. The anti-corrosion topcoat C material is mixed evenly with 20g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane to obtain an anti-corrosion topcoat. The anti-corrosion topcoat is continuously sprayed on the surface of the steel structure substrate 4 coated with the alloy sealing coating 2 to form an amino-modified silane topcoat coating 3, and the thickness of the amino-modified silane topcoat coating 3 is 70μm.
[0145] Example 4
[0146] This embodiment provides a flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure. Figure 1 The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure comprises a flexible alloy coating 1 with a thickness of 90 μm, an alloy sealing coating 2 with a thickness of 110 μm and an amino-modified silane topcoat coating 3 with a thickness of 75 μm, which are sequentially arranged on the surface of a steel structure substrate 4. The sum of the dry film thicknesses of the flexible alloy coating 1, the alloy sealing coating 2 and the amino-modified silane topcoat coating 3 is 275 μm.
[0147] This embodiment also provides a method for preparing a flexible alloy siloxane composite weather-resistant anti-corrosion coating for a steel structure, see Figure 2 , the preparation method specifically comprises the following steps:
[0148] S1: 5g of acrylic modified epoxy conjugated resin, 2g of conductive polyaniline, 50g of copper-zinc alloy, 18g of magnesium-aluminum alloy, 17g of magnesium-lithium alloy, 4g of lanthanum oxide, 4g of cerium trichloride, and 20g of xylene are mixed and stirred to form an anti-corrosion primer, and the anti-corrosion primer is continuously sprayed on the surface of the steel structure substrate 4 to form a flexible alloy coating 1, wherein the thickness of the flexible alloy coating 1 is 90 μm;
[0149] S2: Prepare a 9wt% chlorohexadecane ethanol solution, soak the flaky mica in the chlorohexadecane ethanol solution, wherein the mass ratio of chlorohexadecane to flaky mica is 1:13, filter, wash, and dry to obtain hydrophobic flaky mica; dissolve polydimethylsiloxane in toluene to obtain a coating solution with a mass fraction of 7.5wt%, soak the hydrophobic flaky mica in the coating solution, wherein the mass ratio of polydimethylsiloxane to hydrophobic flaky mica is 1:7.6, take out and solidify to obtain modified flaky mica;
[0150] S3: 15g of E51 epoxy resin, 8g of E20 epoxy resin, 27g of glass flakes, 20g of modified flaky mica and 15g of xylene are mixed and stirred to obtain alloy sealing coating material A, and the alloy sealing coating material A is mixed with 42g of cardanol curing agent to obtain an anti-corrosion intermediate paint, and the anti-corrosion intermediate paint is continuously sprayed on the surface of the steel structure substrate 4 coated with the flexible alloy coating 1 to form an alloy sealing coating 2, wherein the thickness of the alloy sealing coating 2 is 110 μm;
[0151] S4: preparing a calcium fluoride solution with a mass fraction of 8.2wt%, adding a weather-resistant filler to the calcium fluoride solution, wherein the mass ratio of calcium fluoride to the weather-resistant filler is 1.7:100, stirring and mixing, filtering, washing, and drying to obtain a fluorinated weather-resistant filler; mixing a polyurethane resin with anhydrous ethanol to obtain a polyurethane resin solution with a mass fraction of 18wt%, adding the fluorinated weather-resistant filler to the polyurethane resin solution and stirring, wherein the mass ratio of the polyurethane resin to the fluorinated weather-resistant filler is 1.8:10, filtering, and curing to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating;
[0152] S5: 50g of silicone epoxy modified resin SJ-804, 23g of barium sulfate fluoride coated with anti-UV coating, 22g of feldspar powder fluoride coated with anti-UV coating and 20g of butyl acetate are stirred and mixed evenly, and then ground and mixed by ball mill to obtain anti-corrosion topcoat C material. The anti-corrosion topcoat C material is mixed evenly with 28g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane to obtain an anti-corrosion topcoat. The anti-corrosion topcoat is continuously sprayed on the surface of the steel structure substrate 4 coated with the alloy sealing coating 2 to form an amino-modified silane topcoat coating 3, and the thickness of the amino-modified silane topcoat coating 3 is 75μm.
[0153] Comparative Example 1
[0154] This comparative example is based on Example 1, and the difference from Example 1 is that:
[0155] In the flexible alloy coating 1, 70g of zinc powder is used to replace the zinc-aluminum alloy, the magnesium-aluminum alloy, and the magnesium-zinc alloy.
[0156] Comparative Example 2
[0157] This comparative example is based on Example 1, and the difference from Example 1 is that:
[0158] In the amino-modified silane topcoat coating 3, hydroxy acrylic resin is used to replace acrylic polysiloxane resin B6425.
[0159] Comparative Example 3
[0160] This comparative example is based on Example 1, and the difference from Example 1 is that:
[0161] The amino-modified silane topcoat coating 3 uses barium sulfate to replace the barium fluoride sulfate coated in the anti-ultraviolet coating.
[0162] The performance test of the flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 3 was carried out, and the specific process is as follows:
[0163] Test the adhesion of flexible alloy siloxane composite weathering and anti-corrosion coating for steel structure according to GB / T 5210-2006;
[0164] Test the salt spray resistance of flexible alloy siloxane composite weathering and anti-corrosion coating for steel structure according to GB / T 1771-2007;
[0165] According to GB / T 9274-1988, the solvent resistance and acid and alkali resistance of the flexible alloy siloxane composite weathering and anti-corrosion coating for steel structure were tested using mixed acid solution, mixed alkali solution and mixed solvent;
[0166] The moisture and heat resistance of the flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure was tested according to GB / T 1740-2007.
[0167] All test results are shown in Table 1:
[0168] Table 1: Performance test of flexible alloy siloxane composite weathering anticorrosion coating for steel structure of Example 1-Example 4 and Comparative Example 1-Comparative Example 3
[0169]
[0170] Note: The mixed acid solution is 10% sulfuric acid: 5% hydrochloric acid = 1:1 (mass ratio);
[0171] The mixed alkaline solution is 10% sodium hydroxide: 10% potassium hydroxide = 1:1 (mass ratio);
[0172] The mixed solvent is kerosene:xylene:ethanol = 1:1:1 (mass ratio);
[0173] It can be seen from the data in Table 1 that the flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for steel structure prepared in Examples 1 to 4 provided by the present invention has good weather resistance and corrosion resistance.
[0174] It can be seen from the test results of Example 1 and Comparative Example 1 that a single anti-corrosion mechanism has insufficient shielding performance when dealing with a corrosive environment; the use of composite alloy powder can enrich its anti-corrosion mechanism and enhance its anti-corrosion performance. At the same time, the salt inorganic matter in the alloy inhibits the ionization corrosion behavior of the metal when the corrosive medium contacts the alloy, forming a dual protection mechanism and improving the anti-corrosion performance of the coating.
[0175] From the test results of Example 1 and Comparative Example 2, it can be seen that the molecular bond energy of traditional hydroxy acrylic resin is low and it is easy to degrade, thereby limiting the long-term performance of the coating; the use of modified silane resin that is resistant to UV rays, high temperatures and chemical corrosion can extend the service life of the coating in harsh environments. At the same time, the modified silane resin can also provide higher adhesion, thereby effectively reducing the phenomenon of peeling and falling off.
[0176] From the test results of Example 1 and Comparative Example 3, it can be seen that fluorination modification can form a hydrophobic protective layer on the surface of the weather-resistant filler to enhance its anti-corrosion performance. At the same time, the use of anti-ultraviolet resin coating can effectively prevent ultraviolet rays from damaging the filler and substrate, thereby extending the service life of the filler and coating.
[0177] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure, characterized in that: The flexible alloy-siloxane composite weather-resistant anticorrosion coating for steel structure comprises a flexible alloy coating, an alloy sealing coating and an amino-modified silane topcoat coating sequentially arranged on the surface of the steel structure, wherein the sum of the dry film thicknesses of the flexible alloy coating, the alloy sealing coating and the amino-modified silane topcoat coating is 200-300 μm; Wherein, the dry film thickness of the flexible alloy coating is 60-100 μm; The dry film thickness of the alloy sealing coating is 80-120 μm; The dry film thickness of the amino-modified silane topcoat coating is 60-80 μm; The flexible alloy coating comprises ultra-high molecular weight conductive epoxy modified resin, composite alloy powder and rare earth material; The alloy sealing coating comprises epoxy resin, glass flakes, modified flaky mica and amine curing agent; The amino-modified silane topcoat coating comprises a modified silane resin, a fluorinated weather-resistant filler coated with an anti-ultraviolet coating, a diluent and an aminosilane curing agent; The preparation method of the flexible alloy siloxane composite weather-resistant anti-corrosion coating for steel structure is as follows: S1: Mix and stir the ultra-high molecular weight conductive epoxy modified resin, composite alloy powder, rare earth material and xylene to form an anti-corrosion primer, and continuously spray the anti-corrosion primer on the surface of the steel structure substrate to form a flexible alloy coating; S2: preparing a chlorohexadecane ethanol solution, soaking the flaky mica in the chlorohexadecane ethanol solution, filtering, washing, and drying to obtain hydrophobic flaky mica; dissolving polydimethylsiloxane in toluene to obtain a coating solution, soaking the hydrophobic flaky mica in the coating solution, taking it out and curing it to obtain modified flaky mica; S3: mixing epoxy resin, glass flakes, modified flaky mica and xylene, stirring evenly to obtain alloy sealing coating material A, mixing alloy sealing coating material A with an amine curing agent evenly to obtain an anti-corrosion intermediate paint, and continuously spraying the anti-corrosion intermediate paint on the surface of the steel structure substrate coated with the flexible alloy coating to form an alloy sealing coating; S4: preparing a fluorinating agent solution, adding a weather-resistant filler to the fluorinating agent solution, stirring and mixing, filtering, washing, and drying to obtain a fluorinated weather-resistant filler; mixing an anti-ultraviolet resin with anhydrous ethanol to obtain an anti-ultraviolet resin solution, adding the fluorinated weather-resistant filler to the anti-ultraviolet resin solution, stirring, filtering, and curing to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating; S5: After the modified silane resin, the fluorinated weather-resistant filler coated with the anti-ultraviolet coating and the diluent are stirred and mixed evenly, the anti-corrosion topcoat C material is obtained by ball milling and mixing, the anti-corrosion topcoat C material is mixed evenly with the aminosilane curing agent to obtain the anti-corrosion topcoat, and the anti-corrosion topcoat is continuously sprayed on the surface of the steel structure substrate coated with the alloy sealing coating to form an amino-modified silane topcoat coating.
2. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure according to claim 1, characterized in that: The flexible alloy coating comprises the following components in parts by weight: 3-10 parts of ultra-high molecular weight conductive epoxy modified resin; Composite alloy powder 70-95 parts; 1-10 parts of rare earth materials.
3. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure according to claim 2, characterized in that: In the flexible alloy coating: The ultra-high molecular weight conductive epoxy modified resin is acrylic acid modified epoxy conjugated resin and conductive polyaniline; The composite alloy powder is one or a combination of any multiple of zinc-aluminum alloy, magnesium-aluminum alloy, copper-zinc alloy, magnesium-zinc alloy, and magnesium-lithium alloy; The rare earth material is lanthanum oxide and / or cerium trichloride.
4. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure according to claim 1, characterized in that: The alloy sealing coating comprises the following components in parts by weight: Epoxy resin 10-30 parts; Glass flakes 20-35 parts; 10-30 parts of modified flaky mica; 20-50 parts of amine curing agent.
5. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure according to claim 4, characterized in that: In the alloy sealing coating: The epoxy resin is one or a combination of any two or more of E51 epoxy resin, E20 epoxy resin, and E44 epoxy resin; The amine curing agent is polyamide curing agent 650 or cardanol curing agent.
6. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure according to claim 1, characterized in that: The amino-modified silane topcoat coating comprises the following components in parts by weight: 40-60 parts of modified silane resin; 30-50 parts of fluorinated weather-resistant filler coated with UV-resistant coating; 10-30 parts of diluent; 20-30 parts of aminosilane curing agent.
7. The flexible alloy-siloxane composite weather-resistant anti-corrosion coating for steel structure according to claim 6, characterized in that: In the amino-modified silane topcoat coating: The modified silane resin is one or a combination of any two or more of silicone epoxy modified resin SJ-804, acrylic polysiloxane resin B6425, and polyether modified silane resin XT-50; The weather-resistant filler in the fluorinated weather-resistant filler coated with the anti-ultraviolet coating is one or a combination of any two or more of barium sulfate, silicon carbide, feldspar powder and glass powder; The diluent is one or a combination of any two or more of toluene, xylene, anhydrous ethyl acetate, butyl acetate, and propylene glycol methyl ether acetate; The aminosilane curing agent is one of bis-[3-(triethoxysilyl)propyl]amine and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane or any combination thereof.
8. The method for preparing a flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for steel structure according to any one of claims 1 to 7, characterized in that: The preparation method comprises: S1: Mix and stir the ultra-high molecular weight conductive epoxy modified resin, composite alloy powder, rare earth material and xylene to form an anti-corrosion primer, and continuously spray the anti-corrosion primer on the surface of the steel structure substrate to form a flexible alloy coating; S2: preparing a chlorohexadecane ethanol solution, soaking the flaky mica in the chlorohexadecane ethanol solution, filtering, washing, and drying to obtain hydrophobic flaky mica; dissolving polydimethylsiloxane in toluene to obtain a coating solution, soaking the hydrophobic flaky mica in the coating solution, taking it out and curing it to obtain modified flaky mica; S3: mixing epoxy resin, glass flakes, modified flaky mica and xylene, stirring evenly to obtain alloy sealing coating material A, mixing alloy sealing coating material A with an amine curing agent evenly to obtain an anti-corrosion intermediate paint, and continuously spraying the anti-corrosion intermediate paint on the surface of the steel structure substrate coated with the flexible alloy coating to form an alloy sealing coating; S4: preparing a fluorinating agent solution, adding a weather-resistant filler to the fluorinating agent solution, stirring and mixing, filtering, washing, and drying to obtain a fluorinated weather-resistant filler; mixing an anti-ultraviolet resin with anhydrous ethanol to obtain an anti-ultraviolet resin solution, adding the fluorinated weather-resistant filler to the anti-ultraviolet resin solution, stirring, filtering, and curing to obtain a fluorinated weather-resistant filler coated with an anti-ultraviolet coating; S5: After the modified silane resin, the fluorinated weather-resistant filler coated with the anti-ultraviolet coating and the diluent are stirred and mixed evenly, the anti-corrosion topcoat C material is obtained by ball milling and mixing, the anti-corrosion topcoat C material is mixed evenly with the aminosilane curing agent to obtain the anti-corrosion topcoat, and the anti-corrosion topcoat is continuously sprayed on the surface of the steel structure substrate coated with the alloy sealing coating to form an amino-modified silane topcoat coating.
9. The method for preparing a flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for steel structure according to claim 8, characterized in that: In S1: the solid content of the anticorrosive primer is 15-30%; In S2: The mass fraction of the hexadecane chloride ethanol solution is 5-10wt%; The mass ratio of hexachlorodecane to flaky mica is 1:(10-15); The mass fraction of the coating solution is 5-10wt%; The mass ratio of the polydimethylsiloxane to the hydrophobic flaky mica is 1:(5-10).
10. The method for preparing a flexible alloy-siloxane composite weather-resistant and anti-corrosion coating for steel structure according to claim 8, characterized in that: In S3, the solid content of the alloy sealing coating material A is 15-25%; In S4: The fluoriding agent is ammonium fluoride or calcium fluoride; The mass fraction of the fluorinating agent solution is 5-10wt%; The mass ratio of the fluorinating agent to the weather-resistant filler is (1-2):100; The anti-ultraviolet resin is acrylic resin or polyurethane resin; The mass fraction of the anti-ultraviolet resin solution is 10-20wt%; The mass ratio of the anti-ultraviolet resin to the fluorinated weather-resistant filler is (1-2):10.
Citation Information
Patent Citations
Waterborne epoxy flaky ZnAl alloy coating and preparation method thereof
CN115181476A
Anti-corrosion coating system for outer surface of bridge steel
CN117025055A